THE ORGANOLEPTIC AND PHYSIC CHARACTERISTICS AND LACTIC ACID CONTENTS OF YOGHURT WITH COMMERCIAL STARTER ADDED Bifidobacteria bifidum - Tatik Khusniati; Abdul Choliq; Rita Dwi Rahayu (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Bifidobacteria bifidum is probiotic bacteria which inhibit negative bacteria in human ulcer. Adding B. bifidum in commercial yoghurt starter, may increase yoghurt quality. To know yoghurt quality, organoleptic and physic characteristics and lactic acid contents of yoghurt with commercial starter added B. bifidum was observed. B. bifidum concentrations added were 1:4, 2:4, 3:4 (v/v). Organoleptic characteristics were conducted by 18 panelists, physics were visually detected and lactic acid contents were by titration method. The results show that accepted yoghurt characteristics were yoghurt with commercial starter added B. bifidum 1:4 (v/v), and fat yoghurt were more acceptable than that skim. The higher B. bifidum concentrations used, the stronger flavours (after expiry date) and colours (at and after expiry date) of yoghurt, while yoghurt homogenity decreased (at and after expiry date). Fat yoghurt flavours were stronger than that of skim. The higher B. bifidum concentrations and storage times, the higher yoghurt lactic acid contents. Lactic acid contents of fat yoghurt with various starters, were higher than that skim at storage 0-15 days. The fat yoghurt lactic acid contents were 0.99%-1.44%, while that skim were 0.95-1.20%. Based on organoleptic and physic characteristics and lactic acid contents, fat yoghurt were more acceptable that that skim.